2006
DOI: 10.1111/j.1365-2133.2006.07398.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokines and chemokine receptors in the cutaneous lesions of erythema multiforme and Stevens-Johnson syndrome/toxic epidermal necrolysis

Abstract: We have provided further evidence that TNF-alpha is strongly expressed in SJS/TEN lesions and therefore it may be involved in the epidermal necrosis featured in such diseases. IFN-gamma may play an important role both in EM and SJS/TEN. IL-2, IL-5 and IL-13 may contribute to the cutaneous immunoinflammation in these diseases. Chemokine receptors may be involved strongly in the recruitment of inflammatory cells in lesional skin. In our cases we found a sharp polarization towards a Th1 pattern in EM, while the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
85
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 32 publications
9
85
1
1
Order By: Relevance
“…Interestingly, the PP patient exhibited actual values that were similar to the expected value. This result is consistent with the close relationship between psoriasis and Th17 lymphocytes [5]. Furthermore, in psoriasis, there is the paper that Values at the start and after improvement are shown for each cytokine measured clarified the relation between IL-6 and metabolic syndrome [6].…”
Section: To the Editorsupporting
confidence: 84%
“…Interestingly, the PP patient exhibited actual values that were similar to the expected value. This result is consistent with the close relationship between psoriasis and Th17 lymphocytes [5]. Furthermore, in psoriasis, there is the paper that Values at the start and after improvement are shown for each cytokine measured clarified the relation between IL-6 and metabolic syndrome [6].…”
Section: To the Editorsupporting
confidence: 84%
“…Tumor necrosis factor-alpha (TNF-α) has been shown to be strongly expressed in SJS lesions by an Italian group [11] . Authors suggest that IFN-gamma may play an important role in SJS.…”
Section: B Amentioning
confidence: 99%
“…Previously published studies have shown that several cytokines might play an important role in the apoptosis or cytokine flooded inflammation [8,22,23]. Among these recently discovered cytokines are the interleukin (IL), IL-6, IL-8 and monocyte chemo-attractant protein-1 (MCP-1) and all were reported to be unregulated in SJS and TEN [8].…”
Section: Discussionmentioning
confidence: 99%